Securing UAV flying ad hoc wireless networks: authentication development for robust communications - Sen, Muhammet A.; Al-Rubaye, Saba; Tsourdos, Antonios (MDPI, 2025)
Unmanned Aerial Vehicles (UAVs) have revolutionized numerous domains by introducing exceptional capabilities and efficiencies. As UAVs become increasingly integrated into critical operations, ensuring the security of their communication channels emerges as a paramount concern. This paper investigates the importance of safeguarding UAV communication against cyber threats, considering both intra-UAV and UAV–ground station interactions in the scope of the Flying Ad Hoc Networks (FANETs). To leverage the advancements in security methodologies, particularly focusing on Physical Unclonable Functions (PUFs), this paper proposes a novel authentication framework tailored for UAV networking systems. Investigating the existing literature, we categorize related studies into authentication strategies, illuminating the evolving landscape of UAV security. The proposed framework demonstrated a high level of security with lower communication and computation costs in comparison with selected studies with similar types of attacks. This paper highlights the urgent need for strong security measures to mitigate the increasing threats that UAVs encounter and ensure their sustained effectiveness in a variety of applications. The results indicate that the proposed protocol is sufficiently secure and, in terms of communication cost, achieves an 18% improvement compared to the best protocol in the referenced studies.
Keywords: 4606 Distributed Computing and Systems Software; 46 Information and Computing Sciences; 4604 Cybersecurity and Privacy; authentication protocol; physical unclonable function; unmanned aerial vehicles; Analytical Chemistry; 3103 Ecology; 4008 Electrical engineering; 4009 Electronics, sensors and digital hardware; 4104 Environmental management